Wireless Power Transfer via Inductive Coupling - Abu Bakar, Aslina; Idris, Azreme; Razali, Ahmad Rashidy; Zakaria, Mohamad Anuar (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Various types of wireless power transfer method have been developed in recent years. This technology has eventually impacted the human life, especially the way they harvest the electrical energy resources. The most common and the first technology of wireless power created are known as inductive coupling method, which transfers power using magnetism process. This paper proposes the design of an oscillator that produces oscillation frequency at 1MHz for nearfield wireless power transfer, and it is applicable for a short range wireless power transmission only. In conjunction to that, this paper also presents a design of the resonator of an antenna using copper wire in transmitting and receiving the energy transfer for short range transmission of wireless power transfer. The proposed design uses the concept of pad charger where the coil is designed from a pancake coil properties known as flat circular coil. The coil acts as an antenna and magnetic coupled or electromagnetic induced such that when there are changes of current occur in one coil, it will induce the voltage at the other end of the coil, in which the wireless power is transferred between the transmitter and the receive. It can be concluded in this proposed method has the ability to successfully transfer the power between the transmitter and the receiver, even when some obstacles are placed between the coil antennas. Then, a rectifier was used at the receiver to convert the alternating received current to the direct current. The received power is measured to observe the variations at several distances.